Naphthyl piperazines with dual activity as 5-HT1D antagonists and 5-HT reuptake inhibitors - Bueno, Ana B.; Gilmore, Jeremy; Boot, John; Broadmore, Richard; Cooper, Jane; Findlay, Jeremy; Hayhurst, Lorna; Marcos, Alicia; Montero, Carlos; Mitchell, Stephen; Timms, Graham; Tomlinson, Rosemarie; et al. (Bioorganic & medicinal chemistry letters, 2007)
SAR around a known molecule with dual 5-HT(1D) antagonist and 5-HT(transporter) inhibitory activity has led to the discovery of molecules with improved dual activity and reduced cross-reactivity toward other aminergic receptors (5-HT(1B), alpha(1), and D(2)).